Ovule development, megasporogenesis, and megagametogenesis of Fouquieria fasciculata (Willd. ex Roem. & Schult.) Nash (Fouquieriaceae) - Fabiola Soto-Trejo; Sergio Zamudio-Ruiz; Silvia Espinosa-Matías (Botan‪ical Sciences, 2021)
Background: Fouquieriaceae is a small family that consists of a single genus, Fouquieria, with eleven species occurring mostly in arid and semiarid regions of Mexico and the southwestern United States. The development of the ovule and the female gametophyte has been poorly characterized in species of the family; thus, it is proposed to carry out a detailed study on the development of the ovule, megasporogenesis and megagametogenesis in Fouquieria fasciculata.